The trust Teenagers Presently Att ending School Have on Virtual Social Networks - Soler Fonseca, Angela Marcela (Universidad Pedagógica y Tecnológica de Colombia, 2016)
This article approaches the veracity of the trust given through relationships that are generated in the social networks and virtual applications most commonly used by teenagers presently attending school, in two academic institutions in the city of Tunja. The strengthening of trust serves as a dynamic function of social and civic formation in academic relationships, signaling a path that answers to the complexities of school coexistence, even in the virtual context which transcends the academic institution. The multiple case study took place in two academic institutions: a private catholic school and a public secular school. Both schools have an institutional prospectus based on human education and are characterized by the cultural convergence of their actors. Through a mixed method research it was possible to contrast the voices of the users of these media, with the acquired quantitative and qualitative data. As a conclusion, teenagers presently attending school moderately trust relationships generated through social media; in other words, they already think critically about these relationships, fostering prevention and a self-care online. Further, the most commonly used network is Facebook and the mobile application with higher rates of acceptance is WhatsApp, both which are used in and for academic socialization.